Assassination of a Saint : the plot to murder Óscar Romero and the quest to bring his killers to justice - Eisenbrandt, Matt, 1975- (University of California Press, 2017)
"On March 24, 1980, the assassination of El Salvador's Archbishop Óscar Romero rocked that nation and the world. Despite the efforts of many in El Salvador and beyond, those responsible for Romero's murder were never punished for their heinous crime. Assassination of a Saint is the thrilling story of an international team of lawyers, private investigators, and human-rights experts that fought to bring justice for the slain hero. Matt Eisenbrandt, a young lawyer who was part of the investigative team, recounts in this gripping narrative how he and his colleagues interviewed eyewitnesses and former members of death squads while searching for evidence on those who financed them. As they worked towards the only court verdict ever reached for the martyred archbishop's murder, they uncovered information with profound implications for El Salvador and the United States to this day."--Provided by publisher.